Preimmune Control of the Variance of TCR CDR-B3: Insights Gained From Germline Replacement of a TCR Dβ Gene Segment With an Ig DH Gene Segment - Khass, Mohamed; Levinson, Michael; Schelonka, Robert L.; Kapoor, Pratibha; Burrows, Peter D.; Schroeder, Harry W. (Frontiers in Immunology, 2020)
We have previously shown that the sequence of the immunoglobulin diversity gene segment (DH) helps dictate the structure and composition of immunoglobulin heavy chain complementarity determining region 3 (CDR-H3). In order to test the role of germline D sequence on the diversity of the preimmune TCRβ repertoire of T cells, we generated a mouse with a mutant TCRβ DJC locus wherein the Dβ2-Jβ2 gene segment cluster was deleted and the remaining diversity gene segment, Dβ1, was replaced with DSP2.3, a commonly used B cell immunoglobulin DH gene segment. Crystallographic studies have shown that the length and thus structure of TCR CDR-B3 places amino acids at the tip of CDR-B3 in a position to directly interact with peptide bound to an MHC molecule. The length distribution of CDR-B3 has been proposed to be restricted largely by MHC-specific selection, disfavoring CDR-B3 that are too long or too short. Here we show that the mechanism of control of CDR-B3 length depends on the Dβ sequence, which in turn dictates exonucleolytic nibbling. By contrast, the extent of N addition and the variance of created CDR3 lengths are regulated by the cell of origin, the thymocyte. We found that the sequence of the D and control of N addition collaborate to bias the distribution of CDR-B3 lengths in the pre-immune TCR repertoire. Natural selection thus appears to enhance the efficiency of functional TCR production by reducing the likelihood of producing CDR-B3 intervals whose lengths and structures might impede optimal MHC:peptide interactions.